Length–Weight Relationships and Growth Characteristics of Green Mussels (Perna viridis) in the Waters of Tambak Lorok, Semarang - Farazila Ningtias Manurung; Widianingsih Widianingsih; Ita Widowati; Retno Hartati (Jurnal Kelautan Tropis, 2026)
Green mussels (Perna viridis) represent a significant aquaculture commodity in tropical coastal waters, including Tambak Lorok, Semarang, which is subject to substantial anthropogenic influences from urban settlements, port activities, and land-based waste discharges. Understanding the length-weight relationship (LWR) is essential for elucidating growth patterns, physiological conditions, and population dynamics of this species. This study aimed to analyze the spatial-temporal variation of LWR in P. viridis from Tambak Lorok waters while considering water-quality parameters. Sampling was conducted monthly from May to September 2025 across three cultivation stations using random sampling, yielding a total of 750 individuals. Concurrent measurements of environmental parameters, including temperature, salinity, pH, and dissolved oxygen, were recorded during sampling. The logarithmic equation W = aL^b was applied to determine the length-weight relationship, where W represents weight (g) and L denotes shell length (mm). The results revealed a very strong correlation coefficient (R² = 0.908). The allometric coefficient (b) ranged temporally from 2.294 to 2.580 and spatially from 2.144 to 2.562. All b values were consistently below 3, indicating a negative allometric growth pattern, wherein P. viridis in Tambak Lorok tends to elongate faster than it gains weight. These findings contribute valuable baseline data on the population condition and growth characteristics of green mussels in urban coastal ecosystems, supporting sustainable aquaculture management and environmental monitoring programs in the region.